Collection of problems in physical chemistry - Bares, Jiri (Pergamon international library of science, technology, engineering, and social studies., 1961)
Collection of Problems in Physical Chemistry provides illustrations and problems covering the field of physical chemistry. The material has been arranged into illustrations that are solved and supplemented by problems, thus enabling readers to determine the extent to which they have mastered each subject. Most of the illustrations and problems were taken from original papers, to which reference is made. The English edition of this book has been translated from the manuscript of the 2nd Czech edition. It has been changed slightly in some places and enlarged on in others on the basis of further.